Teaching Missiology in and for World Christianity: Content and Method - Phan, Peter C. (International bulletin of mission research, 2018)
The article begins with a brief definition of World Christianity and elaborates three theses for conceiving the relationship between missiology and theology, the understanding and practice of Christian missions, and the teaching of missiology. I argue that outside missiology there is no theology. I also reject the separation between church history and missiology, the division between the historic churches of the West and the mission lands of the rest, and a narrow focus of the goal of Christian missions on conversion and church-planting. Finally, I recommend a shift from church history to history of Christianity.